PENGARUH LATIHAN VARIASI SHOOTING DENGAN INSIDE FOOT DAN INSTEP DRIVE TERHADAP HASIL SHOOTING KE GAWANG PADA ATLET PUTRA SEKOLAH SEPAKBOLA BANDAR KHALIPAH DELI SERDANG USIA 13–15 - SINAGA, BILL VIKTOR; Heri, Zulfan (JURNAL ILMU KEOLAHRAGAAN, 2025)
This study aims to determine the significant effect of shooting variation training using inside foot and instep drive on the results of shooting into the goal in male athletes aged 13-15 years at SSB Bandar Khalipah, Deli Serdang. The method used is an experiment with a one group pre-test post-test design. A sample of 16 athletes was selected using purposive sampling. The training programme was carried out for 6 weeks with a frequency of 3 times per week. Data analysis techniques include Shapiro Wilk normality test, Levene homogeneity test, and paired samples t-test hypothesis testing using SPSS v.25. The results of the analysis showed an increase in shooting scores from a mean pre-test of 50.88 to a post-test of 55.97. Data is normal (p > 0.05) and homogeneous (p = 0.906). The t-test results show tcount = 5.015 > ttable = 2.131, with p < 0.001. Thus, it can be concluded that there is a significant effect of inside foot and instep drive variation training on the results of shooting into the goal in male athletes aged 13-15 years.